1989
DOI: 10.1161/01.str.20.8.1021
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chronic cerebral vasospasm in dogs with ibuprofen and high-dose methylprednisolone.

Abstract: Severe chronic cerebral vasospasm was produced in dog basilar arteries by two injections, 2 days apart, of autologous blood into the cisterna magna of 25 dogs. Treatment with ibuprofen (ra=8) or high-dose methylprednisolone (n=8) after the first injection of blood prevented or reduced angiographic vasospasm. Cerebrospinal fluid concentrations of prostaglandin E 2 , prostaglandin F 2a , 6-ketoprostaglandin F l a (a metabolite of prostacyclin), and thromboxane B 2 (a metabolite of thromboxane A 2 ) were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…A recent report of angioplasty for dilating narrowed arteries indicates that structural changes are a main feature of cerebrovasospasm. 50 Recent clinical and experimental observations by Chyatte 51 and colleagues 52 -53 support the damage hypothesis. Monkeys pretreated with diltiazem were also protected, presumably due to minimization of calcium entry and prevention of calcium overload.…”
Section: Discussionmentioning
confidence: 93%
“…A recent report of angioplasty for dilating narrowed arteries indicates that structural changes are a main feature of cerebrovasospasm. 50 Recent clinical and experimental observations by Chyatte 51 and colleagues 52 -53 support the damage hypothesis. Monkeys pretreated with diltiazem were also protected, presumably due to minimization of calcium entry and prevention of calcium overload.…”
Section: Discussionmentioning
confidence: 93%
“…The interaction between PGE 2 and HbO 2 , both implicated as causative agents in cerebral vasospasm after SAH (Chyatte 1989;Macdonald and Weir, 1991;Pickard et al, 1994;Walker et al, 1983), was examined by studying and comparing PGE 2 -induced constriction before and after incubation with HbO 2 . The PGE 2 -induced constriction in endothelium-denuded porcine basilar arteries in the absence of active muscle tone was potentiated in a concentration-dependent manner after 1-hour incubation with HbO 2 (10 mol/L) (Fig.…”
Section: Prostaglandin E 2 -Induced Vasoconstriction Was Potentiated mentioning
confidence: 99%
“…It has been shown that PGE 2 is the eicosanoid present in the highest concentration in the CSF after SAH (Walker et al, 1983). The levels of PGE 2 in the CSF have been shown to increase 90-fold in dogs (Chyatte, 1989) and up to 250-fold in humans (Pickard et al, 1994) after SAH. In addition, our present experiments showed that constriction induced by PGE 2 was greatly potentiated by HbO 2 , supporting a potential role for PGE 2 in SAH and suggesting a possible mechanism of interaction between these putative causative agents.…”
Section: Figmentioning
confidence: 99%
“…Cytokines and endothelial activation promote changes in smooth muscle cells, while activated leukocytes release potent vasoconstrictors such as endothelin-1 [19]. Agents that block this inflammatory cascade, including corticosteroids and non-steroidal anti-inflammatory agents, have been shown to reduce experimental vasospasm [20]. Thus, a greater degree of early neurogenic inflammatory activation may place patients at higher risk for the subsequent development of disabling cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%